Bibliometric Perspectives on Digital Technologies in Cultural Heritage Analyzing Research Trends and Innovations - Muhtar, Muhtar; Tuhumury, Joana J; Rukoyah, Rukoyah (Eastasouth Institute, 2024)
This study provides a comprehensive bibliometric analysis of research on digital technologies in cultural heritage, focusing on key trends, innovations, and interdisciplinary collaborations. By analyzing co-occurrence networks, author collaborations, and publication density, the study reveals a growing emphasis on the integration of technologies such as augmented reality (AR), virtual reality (VR), and 3D scanning in the preservation and promotion of cultural heritage. These digital tools are increasingly used to create immersive experiences and preserve both tangible and intangible heritage. The study also highlights the rising importance of addressing climate change's impact on heritage sites and explores ethical concerns related to data ownership, authenticity, and equitable access. Despite the many benefits of digital preservation, challenges such as the digital divide and the potential commodification of heritage remain significant obstacles. The analysis underscores the need for interdisciplinary collaborations and the development of sustainable, inclusive digital heritage initiatives to ensure that these technologies benefit all stakeholders. The study concludes by identifying key areas for future research, including the integration of artificial intelligence (AI) and blockchain technologies into cultural heritage management and the exploration of climate change's long-term impact on heritage preservation.